A Simulation Investigation of Fire Smoke Behavior above Urban Street Canyon. (2018) - Tao, Chang-fa; Wang, Kai; Liu, Qin; He, Pei-xiang
Abstract: This paper presents computer simulation investigations on the fire smoke movement above street canyons under a velocity condition. Two buildings with different aspect ratios, when the range of windward building height is 5 17 m and the leeward building height is remain at 18 m, have been considered. Besides, the width of the street canyon has been taken as an important factor to influence the critical velocity here. It is shown that the critical velocity of the fire smoke, which moves from windward building to the leeward building, decreases with the height of windward building firstly, but increases with its further increase. According to the theoretical analysis, it is found that the critical velocity is a function of dimensionless width of street canyon. And a developed model has been developed to predict the critical velocity above the street canyon.